The Marketing Strategy Business to Business of Zein Product - Supriyanto, Muhammad; Fachira, Ira (Journal of Business and Management, 2017)
AbstractMuslim fashion demand in Indonesia has increased from 2010 to 2015. As one Muslim brand Zein Product focus to meet the demand of Muslim men. The number of competitors from other Muslim brand makes Zein has sales are still low. For that Zein need to create a new stategy to be able to increase its sales. On the one hand, Zein has the demand for uniform Muslims from offices and schools. Muslim uniform became one Zein opportunities to increase sales of the company sales. This study aims to find out the characteristics and make recommendations that focus on marketing strategies to gain market business to business uniform for Muslims in offices and schools. By knowing the character and needs of the target market will be in getting the right strategy to be able to get into the business to business market. The method used to obtain information and market needs is to do an interview for the 10 respondents companies and schools in Jakarta and Bandung. The resulting analysis concluded that characteristics of Muslim-style uniform B2B market is that every year companies and schools require uniforms Muslim. Making uniform did earlier in the year for the company and for the mid-year school, the person who makes the decision making uniform is head of a company or manager of the company. MOU and the feedback is very important to cooperate in production. Marketing strategy recommendations that must be done to get a Muslim-style uniform B2B market is servise, quality, and price. To servise start from the proposal deals, good communication during the production process, and after service production. For product quality, the vendor must have the qualities product control division to check the manufacture of uniforms to order. Prices should be made as low as possible due to the school uniform will be resold to students. and they will compare with other vendors. and for the company's production rates are not issues that are important quality of goods and servise.Â Keywords: Characteristics, Recommendation marketing strategy, Business to Business, Muslim-style uniform, Company and School.